2021
DOI: 10.3389/fimmu.2021.672168
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Dampens Immune Responses in In Vitro Activated CD4+ T Cells and Affects Genes Associated With Autoimmune Diseases That Improve During Pregnancy

Abstract: The changes in progesterone (P4) levels during and after pregnancy coincide with the temporary improvement and worsening of several autoimmune diseases like multiple sclerosis (MS) and rheumatoid arthritis (RA). Most likely immune-endocrine interactions play a major role in these pregnancy-induced effects. In this study, we used next generation sequencing to investigate the direct effects of P4 on CD4+ T cell activation, key event in pregnancy and disease. We report profound dampening effects of P4 on T cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 92 publications
2
32
0
Order By: Relevance
“…Indeed, these changes were highly enriched in pathways involved in T-cell activation, the first crucial step involved in T-cell lineage commitment, both in peaks associated to promoter and distal elements. The dampening effect of P4 on T-cell activation are in line with previous findings ( 10 , 11 , 44 ), although here we provide a more fine-grained time series analysis of how P4 affects T-cell activation, in particularly related to T H 1 differentiation. More in-depth analysis revealed that the major TFs regulating these changes were dominated by well-known TFs involved in T-cell activation such as BATF , FOS, FOSL1, FOSL2, JUN and JUNB.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Indeed, these changes were highly enriched in pathways involved in T-cell activation, the first crucial step involved in T-cell lineage commitment, both in peaks associated to promoter and distal elements. The dampening effect of P4 on T-cell activation are in line with previous findings ( 10 , 11 , 44 ), although here we provide a more fine-grained time series analysis of how P4 affects T-cell activation, in particularly related to T H 1 differentiation. More in-depth analysis revealed that the major TFs regulating these changes were dominated by well-known TFs involved in T-cell activation such as BATF , FOS, FOSL1, FOSL2, JUN and JUNB.…”
Section: Discussionsupporting
confidence: 90%
“…To this end, naïve T H cells cultured under T H 1 polarizing conditions alone were compared to T H cells polarized in the presence of P4 ( Figure 1 ). As we have previously shown that P4 induces large transcriptomic changes during T cell activation ( 10 ), we wanted to gain further functional insights into underlying gene regulatory machinery. We therefore used correlation between ATAC-and RNA-seq to identify more robust changes induced by P4 that are transmitted across both omics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can consider the use of the pregnancy-related hormone progesterone, which was shown as early as in 1983, to have anti-inflammatory and immunosuppressive properties (55) because of which it was referred to as "Nature's immunosuppressant" (56). Progesterone suppresses several cellmediated immune activities including the activation and proliferation of lymphocytes (57) and reverses many of the events that occur during T cell activation (58).…”
Section: Manipulation Of Cytokine Profilesmentioning
confidence: 99%